How to be a queer woman: A corpus-assisted critical discourse analysis of online media - Bailey, Aimee (2021)
This thesis examines the discursive identity construction of queer women in contemporary online media. It focuses on two of the most popular entertainment and lifestyle websites for queer women, AfterEllen and Autostraddle, both of which are based in the United States. I assemble a dialogic corpus of advice articles and below-the-line comments from the websites, capturing for the first time the voices of both producers and consumers of online media content on a large scale. This forms the 2-million-word Queer Women’s Advice Corpus. As a genre which instructs queer women in their everyday lives, advice provides a direct route into normativity, the central concept in queer linguistic research. Using a mixed methodology of corpus linguistics and critical discourse analysis, I show how recurrent textual patterns produce normativity in the data.